Clinical Outcomes of Treatment by Percutaneous Coronary Intervention Versus Coronary Artery Bypass Graft Surgery in Patients With Chronic Kidney Disease Undergoing Index Revascularization in Ontario. (January 2015) - Chan, William; Ivanov, Joan; Ko, Dennis; Fremes, Stephen; Rao, Vivek; Jolly, Sanjit; Cantor, Warren J.; Lavi, Shahar; Overgaard, Christopher B.; Ruel, Marc; Tu, Jack V.; Džavík, Vladimír
<x xml:space="preserve">Abstract</x> Background— There is a paucity of data on the comparative effectiveness of percutaneous coronary intervention using contemporary drug-eluting stent (DES) compared with coronary artery bypass graft (CABG) surgery in patients with chronic kidney disease. Methods and Results— A population-based study was performed using the Cardiac Care Network, a provincial registry of all patients undergoing cardiac catheterization in Ontario, to evaluate patients treated with either percutaneous coronary intervention using DES or CABG between October 1, 2008, and September 30, 2011. Chronic kidney disease was defined as creatinine clearance <60 mL/min. A total of 1786 propensity-matched patients from 4006 patients with chronic kidney disease undergoing index revascularization for multivessel disease with either DES or isolated CABG (n=893 each group) were analyzed. Baseline and procedural characteristics between percutaneous coronary intervention and CABG groups were well-balanced, including urgent revascularization priority, diabetes mellitus, left ventricular function, and 3-vessel disease. The 1-, 2-, and 3-year Kaplan–Meier survival analyses in propensity-matched patients favored CABG (93.2% versus 89.3%; 86.6% versus 80.3%; 80.8% versus 71.5%, respectively; P<0.001). The CABG cohort had greater 1-, 2-, and 3-year freedom from major adverse cardiac and cerebrovascular events (89.4% versus 71.2%; 81.9% versus 60.5%; 75.2% versus 51.8%, respectively; P<0.001). Cox regression analysis identified DES use to be associated with greater hazard for late mortality (hazard ratio, 1.58; 95% confidence interval, 1.32–1.90) and major adverse cardiac and cerebrovascular events (2.62; 2.28–3.01; all P<0.001). Conclusions— In this large provincial registry, CABG was associated with improved early and late clinical outcomes when compared with percutaneous coronary intervention using DES in patients with chronic kidney disease undergoing index revascularization.